Prachum botkawīniphon somphōt Krung Rattanakōsin (Khana Kammakān Čhat Ngān Somphōt Krung Rattanakōsin 200 Pī, 1982)
Collection of poems on the Chakri Dynasty and on socioeconomic and cultural conditions in Thailand during the past 200 years.